Patienters upplevelse av delaktighet i sin självdialys — en intervjustudie. (December 2013) - Hamlin, Maria; Jemsson, Monica; Rahm, Ann-Sofie; Henricson, Maria
To suffer from kidney failure requiring dialysis is a major setback on the patient's life situation. The trend in dialysis care is that the patients should be increasingly involved in their own dialysis treatment. The aim of this study was to illustrate the patients' experiences of participation in their own dialysis treatment. A qualitative approach was chosen and the study consists of nine narrative interviews with patients in self-care dialysis who had hemodialysis or peritoneal dialysis at two different hospitals. The results are categorized into the areas of safety and freedom. In order to feel safe the patients must have good knowledge of their disease and dialysis treatment. Patients experience freedom when they participate in their own dialysis treatment and may manage their dialysis schedule. The result also shows that the patients perceive themselves to be healthier when they are able to perform their own dialysis. The major challenge for today's dialysis care is to involve the patients more in their own treatment and to offer them greater flexibility.